Pengaruh Klientilisme terhadap Perilaku Pemilih Masyarakat Kecamatan Sukatani pada Pilkada Kabupaten Bekasi 2012 - Rofieq, Ainur; Nuryono, Rahmat (Political Science Program, Universitas Negeri Semarang, 2016)
This research is motivated by the election of Neneng Hasanah Yasin-Rohim Mintareja who defeated incumbent regional head and deputy head of the Bekasi area in the elections of 2012. The local elections showed a dynamic voter behavior of society. Clientelism practices allegedly occurred in the victory Neneng Hasanah Yasin. The focus of this study is to analyse voting behavior of people in the District Sukatani which has characteristics as agricultural area. Sukatani sub-district is one of the districts that form the basis for Neneng Hasanah Yasin victory. As an analytical tool, the used theory is clientelism. The method used is a quantitative study with a questionnaire as a data collector. Data analysis technique uses cross tabulation. The number of samples in this study is 100 people with a 95% confidence level and a margin of error of 10%. The results of this study indicates that for some indicators clientelism has no difference in voting behavior Sukatani society, such as indicators of the popularity the parents candidates, formal official invitation, informal official invitation, and professional groups invitation. Even for indicators of indebtedness does not exist at all. While indicators have differences on the invitation team is successful candidate.